ANTIBODY PRODUCTION BY CELLS IN TISSUE CULTURE : II. QUALITATIVE AND QUANTITATIVE ASPECTS OF ANTIBODY PRODUCTION (LOCAL HEMOLYSIS IN GUM) BY CELLS OBTAINED FROM LONG TERM CULTURE - Bussard, Alain E. (The Rockefeller University Press, 1966)
By combining a tissue culture method with the detection of antibody-producing cells by local hemolysis in gum it has been possible to follow the immunological activity of cells from tissue fragments for long period of time. These fragments were obtained from lymph nodes or spleens of rabbits immunized by sheep erythrocytes. It was found that, while the immunological activity of the free cells in suspensions decreased fast and disappeared in a few days, the cells attaching on glass could express their activity for at least 3 wk. It is assumed that these cells are the daughters of cells from the fragments which were not active antibody producers at the beginning, but differentiated, during the culture, into cells endowed with two capacities: glass adherence and antibody synthesis. One can further admit that the type of culture employed exerts a selective pressure favoring formation of antibody-producing cells.